If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3x = 5x + 7 Combine like terms: 3x + 3x = 6x 6x = 5x + 7 Reorder the terms: 6x = 7 + 5x Solving 6x = 7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 6x + -5x = 7 + 5x + -5x Combine like terms: 6x + -5x = 1x 1x = 7 + 5x + -5x Combine like terms: 5x + -5x = 0 1x = 7 + 0 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| 260-3x=42x+15 | | -7a^2= | | 49+20(2)= | | -2a+2=1 | | 6-8x=15-36x | | 6-8x=15-6x | | x^2-11x+25=3x+1 | | 6=5x-5 | | 3-y=-31 | | 7-2x=x | | x^2-4x-17=4 | | -4d=5d-17 | | 2x+15-x=14 | | 17a+17b= | | 130.74=179.4*n | | 3X+6=43+X | | 130.6=283.2*n | | 15-6t=-11t | | -11/4x=7 | | 2x+5=7x-4 | | 3w^2+8w+5= | | 13*x^2-8=5 | | (3+5x)(3-5x)= | | 9+3n=(4+5)3-6 | | y=ln(x^2-9) | | 12+8m=100 | | 13*x^2-11=3 | | h/6-29=-21 | | y=(x-5)/(x+5) | | (25+35x)/15=4 | | (3x^2)-(44x)+120=0 | | 8-s=4t+3 |